A biometric fingerprint recognition system utilizing the Scale Invariant Feature Transform (SIFT) algorithm for border crossing - Hamzah N.A.; Jaaz Z.A.; Al-Bakri N.F.; Tawfeq J.F.; Radhi A.D. (Institute of Electrical and Electronics Engineers Inc., 2024)
A biometric machine is a technology-critical machine that recognizes a character primarily based on data from humans or different resident organisms. Biometric structures work well when they have technical information with specific biometric characteristics. Fingerprinting is a technique to identify a person based on facts because it is one of the most widely used authentication techniques and a convenient activity to study. The SIFT algorithm has some drawbacks and is currently widely used because of its overall efficiency, although the efficiency of a single collection is slow. So a system that can be used to identify people by their fingerprints and verify their identity and eventually applied in fingerprint collection and verification at border crossings is particularly important. In this paper, we propose a fingerprint detection system that allows the fingerprint identification process to use image matching even if there are significant differences between the two images. Experimental results show that the algorithm achieves good results in fingerprint processing, both fast and accurate. 2023 IEEE.